Randomized, double-blind, multi-center, phase III clinical trial to evaluate the immunogenicity and safety of MG1109 (egg-based pre-pandemic influenza A/H5N1 vaccine) in healthy adults - Joon Young Song; Min Joo Choi; Ji Yun Noh; Won Suk Choi; Hee Jin Cheong; Seong-Heon Wie; Jin-Soo Lee; Gyu-Jin Woo; Sang Ho Lee; Woo Joo Kim (Human Vaccines & Immunotherapeutics, 2017)
Considering the pandemic potential of avian influenza A/H5N1, development of an effective and well-tolerated vaccine is an essential part of pandemic preparedness plans. This phase III, randomized, double-blind study was conducted to assess the immunogenicity and safety profile of an alum-adjuvanted, whole virion, pre-pandemic influenza A/H5N1 vaccine (MG1109). Healthy individuals were randomly assigned, in a 3:1 ratio, to receive two doses of either MG1109 or placebo containing alum gel. Immunogenicity was determined by hemagglutination inhibition (HI) and microneutralization (MN) assays. Solicited and unsolicited adverse events were assessed after vaccination. Among 420 enrolled subjects, 418 were available for safety analysis, and 298 MG1109 recipients were available for per-protocol immunogenicity analyses. According to the HI assays, after two vaccine doses, all three of the Committee for Medicinal Products for Human Use (CHMP) criteria were met against the vaccine strain for all age groups: seroprotection rate = 74.8% (95% CI: 69.9 – 79.8), seroconversion rate = 67.8% (95% CI: 62.5–73.1), and geometric mean titer ratio (GMTR) = 5.9 (95% CI: 5.4 – 6.4). According to the MN assays, the GMTR was 2.4 (95% CI: 2.1 – 2.7) and 7.0 (95% CI: 6.3 – 7.9) three weeks after the first and second vaccine doses, respectively. Solicited local and systemic adverse events were mostly mild to moderate and were not significantly different between MG1109 and placebo recipients. In conclusion, two-dose administration of alum-adjuvanted H5N1 pre-pandemic influenza vaccine (MG1109) was highly immunogenic and tolerable in adults.